Scope of Varnya Mahakashaya Drugs as A Key Component to Health From A Cosmetic Perspective - Sundar, Bhumika; Gadad, Geeta G (International Research Journal of Ayurveda & Yoga, 2024)
Good health is the ultimatum to longevity. Varna (Skin Complexion) is considered to be an important aspect of health in Ayurveda. Therefore, the quality of skin and its appearance is a key indicator of good health. Deplorable skin conditions impact mental health which may further lead to stress, low personal drive, lack of motivation, fear of communicability of transmitting it to others. At the outset, this article underpins Varnya Mahakashaya of Ayurveda that can be alternatively used as Rasayana and curative medicine than its current extensive use, i.e., cosmetic skin care. Based on analysis and review of classical texts about the application of Varna Mahakashaya (i.e., the formulations that had Varna Mahakashaya as a key ingredient) under three broad categories - Rasayana, Vyadhihara (curative), and Varnya (as a cosmetic) - About 24 formulations lead to effective rejuvenation (Rasayana); 54 formulations were a remedy to skin diseases such as Kushta, Visarpa, Mukhadooshika etc (Vyadhiahara) and eight formulations were typically used for cosmetic purposes (Varnya). Among the group of drugs, Vidari, Yashtimadhu, Chandana and Ushira has been found to be incorporated more in the formulations under the said categories respectively. Therefore, we can conclude that Varnya Mahakashaya not only aids in providing healthy skin or cosmetic purposes, but also plays a vital role in treating a wide variety of skin disorders. This can effectively lead to a balanced, healthy, and stress-free life. In total, Varna Mahakashaya undoubtedly helps improve overall health.